Four putative SWI2/SNF2 chromatin remodelers have dual roles in regulating DNA methylation in Arabidopsis. Issue 1 (December 2018) - Yang, Dong-Lei; Zhang, Guiping; Wang, Lili; Li, Jingwen; Xu, Dachao; Di, Cuiru; Tang, Kai; Yang, Lan; Zeng, Liang; Miki, Daisuke; Duan, Cheng-Guo; Zhang, Huiming; et al.
Abstract DNA methylation is a conserved epigenetic mark that is critical for many biological processes in plants and mammals. In Arabidopsis, the antagonistic activities of RNA-directed DNA methylation (RdDM) and ROS1-dependent active DNA demethylation are key for the dynamic regulation of locus-specific DNA methylation. However, the molecular factors that coordinate RdDM and active demethylation are largely unknown. Here we report that CLSY4 and its three paralogous SWI2/SNF2-type chromatin-remodeling proteins function in both RdDM and DNA demethylation in Arabidopsis. We initially identified CLSY4 in a genetic screen for DNA demethylation factors and subsequently demonstrated that it also is important in RdDM. Comprehensive genetic analyses using single and high order mutants of CLSY family proteins revealed their roles as double agents in the balance between methylation and demethylation reactions. The four CLSY proteins collectively are necessary for the canonical RdDM pathway; at the same time, each CLSY likely mediates DNA demethylation at specific loci where DNA methylation depends on RdDM. These results indicate that the four chromatin-remodeling proteins have dual functions in regulating genomic DNA methylation, and thus provide new insights into the dynamic regulation of DNA methylation in a model multicellular eukaryotic organism.